The genetic advantage of healthy centenarians: unraveling the central role of NLRP3 in exceptional healthspan - Verlinden, Stef F. (Frontiers in Aging, 2024)
Despite extensive research into extending human healthspan (HS) and compressing morbidity, the mechanisms underlying aging remain elusive. However, a better understanding of the genetic advantages responsible for the exceptional HS of healthy centenarians (HC), who live in good physical and mental health for one hundred or more years, could lead to innovative health-extending strategies. This review explores the role of NLRP3, a critical component of innate immunity that significantly impacts aging. It is activated by pathogen-associated signals and self-derived signals that increase with age, leading to low-grade inflammation implicated in age-related diseases. Furthermore, NLRP3 functions upstream in several molecular aging pathways, regulates cellular senescence, and may underlie the robust health observed in HC. By targeting NLRP3, mice exhibit a phenotype akin to that of HC, the HS of monkeys is extended, and aging symptoms are reversed in humans. Thus, targeting NLRP3 could offer a promising approach to extend HS. Additionally, a paradigm shift is proposed. Given that the HS of the broader population is 30 years shorter than that of HC, it is postulated that they suffer from a form of accelerated aging. The term ‘auto-aging’ is suggested to describe accelerated aging driven by NLRP3.